PENGARUH ULASAN PELANGGAN DAN RATING PRODUK TERHADAP MINAT BELI DI E-COMMERCE SHOPEE (STUDI KASUS PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS NUSA NIPA MAUMERE) - Yohanes Don Bosko Lolo; Antonius Phillipus K.Gheta; Nunsio Handrian Meylano (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2026)
This study was conducted due to the increasing dependence of consumers on digital information, such as customer reviews and product ratings, in making purchasing decisions on e-commerce platforms, particularly Shopee. Reviews and ratings are considered indicators of trust that can reduce buyer uncertainty, especially among students who actively shop online. However, the prevalence of invalid reviews and inaccurate product information raises doubts in the decision-making process. Therefore, this study aimed to determine the description of customer reviews, product ratings, and purchase interest, as well as to analyze the partial and simultaneous effects of customer reviews and product ratings on the purchase interest of students at the Faculty of Economics and Business, Nusa Nipa University, Maumere. This study used a quantitative method with an associative approach that aimed to test the causal relationship between the variables of customer reviews (X1), product ratings (X2), and purchase interest (Y). Data were collected through a survey using a Likert scale questionnaire distributed to 94 students selected using the Slovin formula from a total population of 1,473 students of the Faculty of Economics and Business. The data sources consisted of primary data in the form of questionnaire results and secondary data in the form of literature, journals, and supporting documents. The results of the study based on descriptive analysis showed that Customer Reviews, Product Ratings, and Purchase Interest are in the “Good” category. The t-test results showed that, partially, customer reviews (X1) had a significant effect on purchase interest, as indicated by a t-count of Product ratings (X2) were also proven to have a significant effect on purchase interest with a t-value of Simultaneously, both variables contributed 44.1% to purchase interest, while the remaining 55.9% was influenced by other factors outside the scope of this study. The study concludes that reviews and ratings are important sources of information that shape consumer confidence before purchasing. Recommendations include the need for platforms to display verified reviews, improve the quality of rating information, and provide incentives for users who give honest reviews to increase the credibility of information for young consumers.